2018
DOI: 10.1063/1.5009765
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and structural evidence of mesoscopic aggregation in phosphonium ionic liquids

Abstract: Mesoscopic aggregation in aprotic ionic liquids due to the microphase separation of polar and non-polar components is expected to correlate strongly with the physicochemical properties of ionic liquids and therefore their potential applications. The most commonly cited experimental evidence of such aggregation is the observation of a low-q pre-peak in the x-ray and neutron scattering profiles, attributed to the polarity alternation of polar and apolar phases. In this work, a homologous series of phosphonium io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…In this representation, it is evident that an additional relaxation is present in each experiment at rates slower than that of the primary structural relaxation in agreement with prior studies. [27,42,43] In neat C n MIm BF 4 ionic liquids, the emergence of the slow dynamics was found to coincide with the onset of solvophobic aggregation, as evidenced by the development of the x-ray scattering pre-peak, and by a comparison between the relaxation rates with those previously obtained by neutron spin echo spectroscopy. [27,[29][30][31] Therefore, the slow relax-ations were attributed to fluctuations of the mesoscale aggregates at timescales longer than the structural relaxation.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…In this representation, it is evident that an additional relaxation is present in each experiment at rates slower than that of the primary structural relaxation in agreement with prior studies. [27,42,43] In neat C n MIm BF 4 ionic liquids, the emergence of the slow dynamics was found to coincide with the onset of solvophobic aggregation, as evidenced by the development of the x-ray scattering pre-peak, and by a comparison between the relaxation rates with those previously obtained by neutron spin echo spectroscopy. [27,[29][30][31] Therefore, the slow relax-ations were attributed to fluctuations of the mesoscale aggregates at timescales longer than the structural relaxation.…”
mentioning
confidence: 56%
“…In neat C n MImBF 4 ionic liquids, the emergence of the slow dynamics was found to coincide with the onset of solvophobic aggregation, as evidenced by the development of the X-ray scattering prepeak and by a comparison between the relaxation rates with those previously obtained by neutron spin echo spectroscopy. 27,[29][30][31]45,46 Therefore, the slow relaxations were attributed to fluctuations of the mesoscale aggregates at time scales longer than the structural relaxation. This attribution is further substantiated by Yamaguchi's recent computational work, which shows that a cross-correlation exists between the shear stress relaxation and the slow relaxation of the domain structure corresponding to the scattering prepeak.…”
mentioning
confidence: 99%
“…This relaxation emerges around 220 K, corresponding to TL−L observed in the WAXS and Raman data. The slow relaxation in ILs has been linked to interfacial polarization arising from mesoscale ordering of the polar and nonpolar domains in the liquid structure (31,32). This process that appears in the low-temperature liquid II state is directly connected to the increase in εs shown in Fig.…”
Section: Significancementioning
confidence: 99%
“…Hereafter, in the present paper, the Qa and Qp cations with four normal alkyl groups are denoted as N abcd + and P abcd + , respectively, where a , b , c , and d represent the number of carbon atoms of the alkyl groups. The bulk structure of these ILs has been studied by small-angle X-ray scattering, wide-angle X-ray scattering, ,, NMR, Raman scattering spectroscopy, broadband dielectric spectroscopy, , and MD simulation. ,, In contrast to the bulk studies, a limited number of studies have focused on the surface structure of QaILs, ,,, , some of which used cations having more than two alkyl chains. ,,,,, A comparison between N 6444 + and C 4mim + has been made by Aliaga and Baldelli using SFG, revealing that the butyl chain in both the cations has similar orientational preferences at the surface. The same research group also studied the surface of a series of [N 11 i ‑Pr n + ]­[TFSA – ] ( i -Pr = isopropyl, n = 3, 4, 6, 10), which revealed that the orientation of the alkyl chain strongly depends on the length and that the longer alkyl chains have gauche conformation.…”
Section: Introductionmentioning
confidence: 99%